Morphological, phytochemical, and proteomic responses of Andrographis paniculata nees. to salt stress - Talei, Daryush (2012)
Andrographis paniculata Nees. is a medicinal plant belonging to the family Acanthaceae. The plant is important due to its pharmaceutical curative compound called diterpenoids. The compound is extracted from vegetative parts of the plant which was cultivated in the field from seeds. However, growing the plant is challenging especially in arid and semi-arid regions where salt concentration is relative high. In different parts of the world, the plant exists in various accessions but none of them was properly characterized for its level of salt tolerance. Therefore, the present study was conducted to determine the salt tolerance thresholds of various accessions of the plant, and finally, to characterize the accessions for their physiological, phytochemical and proteomic responses to elevated levels of salt. Salt tolerance thresholds of the various accessions of the plant were determined by exposing 6 of the accessions to different salt concentrations and exposure times at seedling. The experiments were carried out in a split split plot arrangement based on the RCBD. Based on salt tolerance threshold results various dependent parameters related to physiological, biochemical and proteomic responses of the 32 different accessions of the plant were evaluated at seedling and mature stages. Changes in metabolites and proteomes weremonitored by using HPLC and 2D-polyacrylamide gel electrophoresis, respectively. It was found that the tolerance threshold of the plant was 12 dSm-1 for 15-day of exposure time. Based on the salt tolerance index of individual accession, the plant could be grouped into salttolerant, moderately salt-tolerant and salt-sensitive accessions. When exposed to a high salt concentration, the tolerant accessions accumulated higher concentrations of proline, K+, Ca2+and andrographolide, and lower oncentration of Na+ than the sensitive ones, suggesting a salt tolerance response dictated by metabolite and ion adjustments. However, the levels ofphotosynthetic parameters were decreased in all of the accessions, which indicate that the salt stress directly reduced photosynthesis in the plant. Andrographolide content was positively correlated with salt concentration; the higher concentration of the salt the larger increase in andrographolide was observed. The concentration of three main phytochemicals (andrographolide, neoandrographolide and 14-deoxy-11, 12-didehydroandrographolide)evaluated were also positively correlated with salt tolerance index and were negatively correlated with proline content. Overall, these patterns resemble the plant’s salt tolerance responses based on physiological and phytochemical performances. At proteomic level, the tolerant accessions showed dissimilar SDS-PAGE banding patterns of soluble leaf protein of the plant exposed to high salt concentrations. These proteins were further analyzed by 2D gel electrophoresis in combination with a spot protein analysis by using the PDQuest software.The analysis led to the detection of 32 induced proteins and 12 up-regulated proteins in the leaf and root of the salt-treated plants. Of the 44 detected proteins, 12 were sequenced with three of them matched superoxide dismutase, ascorbate peroxidase and ribulose-1, 5-bisphosphate oxygenase whereas the rest were unknown. The three known proteins are generally associated with plant response to environmental stresses and could represent general stress proteins in the present study. Together, the proteomic data and the diverse physiological and phytochemical reactions demonstrated by the different accessions of the plant to salt stress would potentially be used as salt tolerance indicators in the plant’s breeding program for salt tolerance improvement.